InHand: mobile professional context and location aware tool - Neves, Paulo Alexandre (2008)
A travel book salesman needs current information that leads to the development of an information system about costumers, supplies, orders and the books themselves. Such scenario demands maximum mobility and rapid information retrieval that points to a mobile application. The paper presents an application developed for local and remote use, called InHand, that is context-aware, presenting information related to the current user context and provides location-aware support through the use of the Global Positioning System (GPS). The location system keeps track of a client ’s location, schedules client visits for a given day, help user navigate through a map using real-time position acquisition, and gather the pathway followed by a user on a given day. The application has two channels: server and mobile client. The mobile client can synchronize data with the server, and relies on a local database to minimize wireless traffic to a minimum. We use Remote Data Access and Web Services to access remote data in a convenient way. Although the application is designed with book selling in mind, the concept is perfectly extendable to other fields of application.